Identificação de RNAs longos não codificantes SNHGs associados com fatores de pior prognóstico em câncer cervical: uma revisão sistemática da literatura - ARAUJO, Eleilde Almeida (2023)
Introduction: Cervical Cancer (CC) is the third most common type of cancer amongst women in Brazil. More than 17,000 cases were estimated for 2023, with about 800 of them in the state of Maranhão. Worse prognostic factors are associated to a lower survival rate in patients with this type of disease. The aberrant expression of non-coding RNAs (ncRNAs) has been associated with these factors, pointing to these biomolecules as potential biomarkers. Among the ncRNAs, we highlight the long non-coding RNAs (lncRNAs) of the class SNHGs (small nucleolar host gene), which are still underexplored for CC. Objective: To identify SNHGs related to worse prognostic factors in cervical cancer through a systematic literature search. Methods: This study was conducted according to the PRISMA-scR protocol, using the PICO strategy. Then, a literary search was carried out in the following sources: PubMed, ScienceDirect, Lilacs and Medline. After the application of inclusion and exclusion criteria, we extracted information such as: expression level, sample type, techniques addressed, biological function, clinical significance, target elements (microRNAs and pathways) regulated by SNHGs. Results: Out of a total od 3,803 studies, we selected 12 that contemplated 8 SNHGs (GAS5, SNHG5, SNHG7, SNHG12, SNHG14, SNHG16, SNHG17 and SNHG20) associated to CC. All, except for GAS5, presented an overexpression that was associated to worse prognosis factors such as: proliferation, migration, invasion, apoptosis, lymph node metastasis, FIGO and tumor size, degree of differentiation in CC. Out of the 8 SNHGs studied, 7 (SNHG5, SNHG12, SNHG14, SNHG16, SNHG17, SNHG20 and SNHG2/GAS5) can act as molecular sponges of miRNAs. Conclusion: Overall, this family of SNHGs is part of an interacting network, regulating important pathways for carcinogenesis. Thus, in the future, they may be used as biological markers and therapeutic targets in their wide applications in diagnosis and treatment. Further research is necessary to understand the role of SNHGs in cervical cancer.